Expression of laminin‐5 gamma 2 chain predicts invasion of extramammary Paget's disease cell. Issue 1 (21st October 2020) - Tohmatsu, Yuuko; Imura, Johji; Sakai, Takeshi; Takagi, Kohji; Minamisaka, Takeshi; Tanaka, Shinichi; Noguchi, Akira; Nakajima, Takahiko; Nagata, Takuya; Makino, Teruhiko; Shimizu, Tadamichi; Fujii, Tsutomu
Abstract : Extramammary Paget's disease (EMPD) is a rare malignant skin neoplasm characterized by intraepidermal proliferation of tumor cells. The tumor cells of EMPD may sometimes invade into the dermis or metastasize into the regional lymph nodes. Several studies have proposed mechanisms underlying the increased invasiveness of EMPD; however, molecular markers indicating invasiveness have yet to be well characterized. Laminin‐5 (Lam‐5), a heterotrimer composed of three chains (α3, β3, and γ2), is a major component of the basement membrane in many tissues. One of the chains, Lam‐5 γ2, is a marker of invasion, because it often develops as a monomer in malignant neoplasms. We investigated the expression of Lam‐5 γ2 and its role for the invasiveness in EMPD. Paraffin‐embedded specimens of EMPD obtained from 36 patients were examined immunohistochemically for Lam‐5 γ2. The cases adopted into this study comprised 16 cases of intraepidermal lesions and 20 cases with dermal invasion. The basement membrane seen in normal skin disappeared in one‐third of non‐invasive cases and in most invasive cases. The disappearance of Lam‐5 γ2 in the basement membrane and its cytoplasmic expression was more observed in the invasive cases than non‐invasive cases. Expression of Lam‐5 γ2 may be a biological marker to predict invasiveness of EMPD.